THE USEFULNESS OF ECOLOGICAL NICHE CONCEPTS IN UNDERSTANDING PLANT COMMUNITIES - Robiansyah, Iyan (Buletin Kebun Raya, 2012)
Plant communities have been attracting many scientists due to their complexity and unclear underlying mechanisms that support it. How large numbers of competing plant species manage to coexist, for instance, is one of the major unresolved questions in plant community ecology. Ecological niche concept is a classical theory which tries to address this question. The development of this concept will be presented in this paper. Recent studies, although few in number and incomplete in many ways, do suggest that plants segregate along various environmental niche axes. Although it is unlikely that niche separation along environmental axes is the only mechanism of coexistence in any large community, the evidence now suggests that ecological niche concept plays a more significant role than has been previously appreciated.